Repair of Posterior Vaginal Wall Defect Using Biologic Graft for Stage III-POP-Q Pelvic Organ Prolapse in a Patient with History of a J-Pouch. (27th July 2020) - Azadi, Ali; Casey, Stephanie; Ramanujam, Paravasthu; Tehranchi, Darya; Ostergard, Donald
Abstract : Surgical correction is considered in women with symptomatic pelvic organ prolapse (POP). There is an expected increase in the prevalence of surgical correction due to an aging population within the United States. Individuals with previous colorectal surgery present a unique challenge considering the changes in pelvic anatomy. This case discusses the challenges of posterior colporrhaphy in a patient with previous, remote J-pouch surgery. In traditional posterior colporrhaphy, randomized controlled trials have not shown any benefit of graft augmentation (Maher, 2016). However, the utilization of a biologic graft to improve anatomical correction is discussed in this unique case. Short term anatomical success was obtained without immediate complications in the postoperative period. In a patient with a history of ulcerative colitis with colorectal resection and a J-pouch, surgery can be challenging due to alterations of pelvic anatomy. Modification of the standard surgical approach may be required to achieve success.